Discretionary Evidence Loaning as Property Rights Protection for Victims of Motor Vehicle Theft: An Empirical Study on the Modernized Criminal Justice Paradigm - Subekti Subekti; Maldine Ikhtiarsyah Putra; Yoyok Ucuk Suyono; Ernu Widodo; Donny Irawan (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
Motor vehicle theft remains a dominant conventional crime that challenges local law enforcement stability. Although recovering stolen vehicles represents a success for investigators, it paradoxically triggers secondary victimization when those vehicles are impounded in police custody for extended periods as court evidence. This study aims to analyze the legal protections provided to victims regarding their property rights and identify the technical-legal obstacles faced by investigators in the field amid the transition toward Indonesia's modernized criminal justice framework. Using empirical legal research with fact and statute approaches, data were gathered through in-depth interviews with investigators at the Tanjungpinang City Police Resort (Polresta Tanjungpinang) and affected victims. The results indicate that legal protection is effectively delivered through transparent Case Progress Reports (SP2HP) and a fast-track, cost-free